Frontispiece: α‐Borylated Phosphorus Ylides (α‐BCPs): Electronic Frustration within a C−B π‐Bond Arising from the Competition for a Lone Pair of Electrons. Issue 59 (23rd October 2018) - Radius, Michael; Breher, Frank
Abstract : The concept and the first example for electronic frustration within a C–B π‐bond was inspired by thoughts about the long‐known substance class of α‐borylated phosphorus ylides (α‐BCP). This cover illustrates the nature of the strained C−B π‐bond arising from the competition for a lone pair of electrons and the found reactivity with, for example, CO as well as the value of looking back from time to time and considering old knowledge in the light of new insights; for more details, see the Communication by F. Breher and M. Radius on page 15744 ff.